Hubungan Antara Variasi Sudut dengan Nilai Periode pada Bandul Menggunakan Mikrokontroller Arduino - Abdul Rafid Fakhrun Gani (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2021)
Pendulum motion is an example of simple harmonic motion which undergoes back and forth motion through its equilibrium point regularly. In the motion of a pendulum there is a period which is the time it takes to travel one path of the pendulum. In determining the period of the pendulum, there are quantities that affect the period of the pendulum, one of which is the initial deviation. This study aims to prove and determine the relationship between the magnitude of the pendulum deviation with the value of the pendulum period. The value of the period of the pendulum at an angle of <100 will be different from the value of the period at an angle of >100. Experiments were carried out using Arduino as a digital practicum tool, this is because the digital practicum tool has a high accuracy value and has a low relative error. The angle variations selected are 100, 200, 300, and 400, the results obtained in the experiment show that there is a significant difference between the coefficient of variation of the pendulum and the coefficient of the pendulum period.